Pain Associated with Wound Care Treatment among Buruli Ulcer Patients from Ghana and Benin - Alferink, Marike (PLoS One, 2015)
Buruli ulcer (BU) is a necrotizing skin disease caused by Mycobacterium ulcerans. People living in remote areas in tropical Sub Saharan Africa are mostly affected. Wound care is an important component of BU management; this often needs to be extended for months after the initial antibiotic treatment. BU is reported in the literature as being painless, however clinical observations revealed that some patients experienced pain during wound care. This was the first study on pain intensity during and after wound care in BU patients and factors associated with pain. In Ghana and Benin, 52 BU patients above 5 years of age and their relatives were included between December 2012 and May 2014. Information on pain intensity during and after wound care was obtained during two consecutive weeks using the Wong-Baker Pain Scale. Median pain intensity during wound care was in the lower range (Mdn = 2, CV = 1), but severe pain (score > 6) was reported in nearly 30% of the patients. Nevertheless, only one patient received pain medication. Pain declined over time to low scores 2 hours after treatment. Factors associated with higher self-reported pain scores were; male gender, fear prior to treatment, pain during the night prior to treatment, and pain caused by cleaning the wound. The general idea that BU is painless is incorrect for the wound care procedure. This procedural pain deserves attention and appropriate intervention.